Inhibition of Viability, Proliferation, Cytokines Secretion, Surface Antigen Expression, and Adipogenic and Osteogenic Differentiation of Adipose-Derived Stem Cells by Seven-Day Exposure to 0.5 T Static Magnetic Fields - Jian Wang; Bo Xiang; Jixian Deng; Darren H. Freed; Rakesh C. Arora; Ganghong Tian (Stem Cells International)
After seven-day exposure to 0.5-Tesla Static Magnetic Field (SMF), Adipose-derived Stem Cells (ASCs) and those labeled by superparamagnetic iron oxide (SPIO) nanoparticles were examined for viability by methyl thiazol tetrazolium (MTT) assay, proliferation by cell counting and bromodeoxyuridine (BrdU) incorporation, DNA integrity by single cell gel electrophoresis, surface antigen by flow cytometry analysis, and the expression of cytokines and genetic markers by reverse transcription-PCR and underwent adipogenic and osteogenic differentiation assessed by quantifying related specific genes expression. The SMF slightly reduced cell viability and proliferation and inhibited the expression of CD49d, CD54, and CD73 but did not damage DNA integrity. The SMF slightly downregulated the expression of cytokines including Vascular Endothelial Growth Factor (VEGF), Insulin-like Growth Factor-1 (IGF-1), Transforming Growth Factor Beta 1 (TGF-β1), genetic markers comprising Stem Cell Antigen-1 (Sca1), Octamer-4 (Oct-4), ATP-binding Cassette Subfamily B Member 1 (ABCB1), adipogenic marker genes containing Lipoprotein Lipase (LPL), Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ), and osteogenic marker genes including Secreted Phosphor-protein 1 (SPP1) and Osterix (OSX). Exposure to 0.5 T SMF for seven days inhibited viability, proliferation, surface antigen expression, cytokine secretion, stem cell genetic marker expression, and adipogenic and osteogenic differentiation but did not affect the DNA integrity in ASCs with or without SPIO labeling.